2022
DOI: 10.3390/biology11121722
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Biological Maturation Level, Muscle Strength, and Muscle Power in Adolescents

Abstract: The purpose of this study was to investigate the relationship between adolescents’ biological maturation level and their muscle power, as well as their overall muscle strength. Overall, 691 adolescents (414 boys and 277 girls) aged 12.01–11.96 (measured for body mass, body height as well as vertical jump, muscle power, and muscle strength). There was a statistically significant difference in terms of average right and left grip strength, vertical jump, and power in the late maturation group. For the body heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…There was an increase in body height and mass for both groups, with no significant between-group differences. Maturation was not considered within this study, thus it should be noted that the body growth of participants could influence the results ( Yapici et al, 2022 ). Nevertheless, specific to body mass, since BF% from pre- to post-testing did not change, it is possible that there was an increase in lean body mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an increase in body height and mass for both groups, with no significant between-group differences. Maturation was not considered within this study, thus it should be noted that the body growth of participants could influence the results ( Yapici et al, 2022 ). Nevertheless, specific to body mass, since BF% from pre- to post-testing did not change, it is possible that there was an increase in lean body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also shown how strength training interventions can improve muscular power in adolescent athletes ( Slimani et al, 2018 ; Wakely et al, 2022 ). Although there was an increase in muscular strength, it is important to note that adolescents may still be growing, and the strength and power increases could have been influenced by the process of maturation within this age group ( Yapici et al, 2022 ). Nonetheless, given the ~10–11% increases in grip strength, ~57–58% increases in LBD scores, ~19–25% increases in MBT distance, and 10–14% increases in VJ across both groups, it could be expected that the intervention was successful in improving strength and power of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Related to researching strength and big muscles, Gillen et al [ 35 ] indicated that variations can be linked to biological maturation [ 35 ]. However, biological maturation has been found to be highly correlated with teenage muscle strength and power [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has reported a significant association between handgrip strength and jump performance ( França et al, 2023 ; Maurya et al, 2023 ), which may help explain the findings. Moreover, when analyzing and interpreting handgrip strength during childhood and adolescence, it is essential to consider the influence of biological maturation and growth, since changes in muscle mass and muscle fiber size may be the contributory factors ( Gómez-Campos et al, 2018 ; Yapici et al, 2022 ; Wind et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%